E-Commerce Technology In International Trade - T Rohmawati; H Amirul (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this research is to discover further the development of trade influenced by technology. This research used descriptive analysis method which is a method that aims to collect actual information in detail that describes the existing phenomena, identify problems, or check the conditions which then make the comparisons and evaluations, decide what others do in dealing with the same problem and learn from experience to set plans and decisions in the future. The results it show that e-Commerce does create opportunities for B2B businesses. In conclusion, with the continued growth of the Indonesian economy and the high level of confidence of small and medium businesses (SMEs), more and more SMEs can expand their businesses abroad.